漸化式の基本
(1)等差数列
\[
a_{n+1}=a_{n}+d
\]
の一般項は、
\[
a_{n}=a_{1}+(n-1)d
\]
となる。
又は\(a_{c}\)が既知のとき
\[
a_{n}=a_{c}+\left(n-c\right)d
\]
となる。
(2)等比数列
\[
a_{n+1}=ra_{n}
\]
の一般項は
\[
a_{n}=a_{1}r^{n-1}
\]
となる。
又は\(a_{c}\)が既知のとき
\[
a_{n}=a_{c}r^{n-c}
\]
となる。
(3)階差数列
\[
a_{n+1}=a_{n}+f\left(n\right)
\]
の一般項は
\[
a_{n}=a_{1}+\sum_{k=1}^{n-1}f\left(k\right)
\]
となる。
又は\(a_{c}\)が既知のとき
\begin{align*}
a_{n} & =a_{c}+\sum_{k=c}^{n-1}f\left(k\right)
\end{align*}
となる。
(4)階比数列
\[
a_{n+1}=f\left(n\right)a_{n}
\]
の一般項は
\[
a_{n}=a_{1}\prod_{k=1}^{n-1}f\left(k\right)
\]
となる。
又は\(a_{c}\)が既知のとき
\[
a_{n}=a_{c}\prod_{k=c}^{n-1}f\left(k\right)
\]
となる。
(1)
\begin{align*} a_{n} & =a_{1}+\sum_{k=1}^{n-1}\left(a_{k+1}-a_{k}\right)\\ & =a_{1}+\sum_{k=1}^{n-1}d\\ & =a_{1}+(n-1)d \end{align*}
\(a_{c}\)が既知のとき
\begin{align*} a_{n} & =a_{c}+\sum_{k=c}^{n-1}\left(a_{k+1}-a_{k}\right)\\ & =a_{c}+\sum_{k=c}^{n-1}d\\ & =a_{c}+\left(n-c\right)d \end{align*}
(2)
\(a_{1}\ne0\land r\ne0\)ならば\(a_{n}\ne0\)なので、
\begin{align*}
a_{n} & =a_{1}\prod_{k=1}^{n-1}\frac{a_{k+1}}{a_{k}}\\
& =a_{1}\prod_{k=1}^{n-1}r\\
& =a_{1}r^{n-1}
\end{align*}
\(a_{1}=0\lor r=0\)のときもこの式は成り立つ。ただし\(0^{0}=1\)とする。
\(a_{c}\)が既知のとき
\begin{align*} a_{n} & =a_{c}\prod_{k=c}^{n-1}\frac{a_{k+1}}{a_{k}}\\ & =a_{c}\prod_{k=c}^{n-1}r\\ & =a_{c}r^{n-c} \end{align*}
(2)別解
\(a_{1}\ne0\land r\ne0\)ならば\(a_{n}\ne0\)なので、
\begin{align*}
a_{n} & =\exp\left(\log a_{n}\right)\\
& =\exp\left(\log a_{1}+\sum_{k=1}^{n-1}\left(\log a_{n+1}-\log a_{n}\right)\right)\\
& =\exp\left(\log a_{1}+\sum_{k=1}^{n-1}\log r\right)\\
& =\exp\left(\log\left(a_{1}r^{n-1}\right)\right)\\
& =a_{1}r^{n-1}
\end{align*}
\(a_{1}=0\lor r=0\)のときもこの式は成り立つ。ただし\(0^{0}=1\)とする。
(3)
\begin{align*} a_{n} & =a_{1}+\sum_{k=1}^{n-1}\left(a_{k+1}-a_{k}\right)\\ & =a_{1}+\sum_{k=1}^{n-1}f\left(k\right) \end{align*}
\(a_{c}\)が既知のとき
\begin{align*} a_{n} & =a_{c}+\sum_{k=c}^{n-1}\left(a_{k+1}-a_{k}\right)\\ & =a_{c}+\sum_{k=c}^{n-1}f\left(k\right) \end{align*}
(4)
\(a_{1}\ne0\land\prod_{k=1}^{n-1}f_{k}\ne0\)ならば\(a_{n}\ne0\)なので、
\begin{align*}
a_{n} & =a_{1}\prod_{k=1}^{n-1}\frac{a_{k+1}}{a_{k}}\\
& =a_{1}\prod_{k=1}^{n-1}f\left(k\right)
\end{align*}
\(a_{1}=0\lor\prod_{k=1}^{n-1}f_{k}=0\)のときもこの式は成り立つ。
\(a_{c}\)が既知のとき
\begin{align*} a_{n} & =a_{c}\prod_{k=c}^{n-1}\frac{a_{k+1}}{a_{k}}\\ & =a_{c}\prod_{k=c}^{n-1}f\left(k\right) \end{align*}
(4)別解
\(a_{1}\ne0\land\prod_{k=1}^{n-1}f_{k}\ne0\)ならば\(a_{n}\ne0\)なので、
\begin{align*}
a_{n} & =\exp\left(\log a_{n}\right)\\
& =\exp\left(\log a_{1}+\sum_{k=1}^{n-1}\left(\log a_{k+1}-\log a_{k}\right)\right)\\
& =\exp\left(\log a_{1}+\sum_{k=1}^{n-1}\left(\log f\left(k\right)\right)\right)\\
& =\exp\left(\log\left(a_{1}\prod_{k=1}^{n-1}f\left(k\right)\right)\right)\\
& =a_{1}\prod_{k=1}^{n-1}f\left(k\right)
\end{align*}
\(a_{1}=0\lor\prod_{k=1}^{n-1}f_{k}=0\)のときもこの式は成り立つ。
ページ情報
タイトル | 漸化式の基本 |
URL | https://www.nomuramath.com/dbilkque/ |
SNSボタン |